Cost and Transmission Requirements for Reliable Solar Electricity from Deserts in China and the United States - Labordena, Mercè; Lilliestam, Johan (Energy Procedia, 2015)
Concentrating solar power (CSP) with thermal storage can help integrate the increasing amounts of intermittent renewables in China and the US. An interconnected fleet of CSP stations in the deserts of China and the US can supply fully dispatchable or baseload electricity for the demand centers, via long-distance HVDC lines. In China the solar power cost at the point of delivery is at or below 20 c/kWh, if the CSP fleet utilizes the solar resources in Tibet. In the US regional weather patterns make it economically unfeasible, although technically possible, to generate fully dispatchable CSP.
CRIS-Team Scopus Importer:2023-06-14
Keywords: China; Concentrating solar power; decarbonization; electricity; HVDC; reliability; transmission; United States